Individuals of refugee background resettled in regional and rural Australia: A systematic review of mental health research. (19th October 2021) - Hawkes, Clare; Norris, Kimberley; Joyce, Janine; Paton, Douglas
Abstract: Introduction: The Australian Government aims to increase the number of individuals on humanitarian resettlement visas allocated to regional locations to 50% by the year 2022. A significant issue with this, given the substantive body of research identifying that refugee populations face chronic mental health concerns during resettlement, is the lack of health‐related research focusing on the resettlement of individuals of refugee background to rural and regional locations in Australia, especially in the area of mental health. Objective: To provide a foundation for rectifying this omission, this review is the first to synthesise mental health research focusing on individuals of refugee background specifically resettled to rural and regional locations in Australia. Design: The review was conducted in line with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guideline. Findings were synthesised using thematic analytic techniques. Findings: 14 relevant studies (3 quantitative, one mixed‐method, 10 qualitative) were identified. Findings indicated that individuals of refugee background resettled in rural and regional Australia not only experienced higher levels of psychological distress than the general population but also had significant difficulty and limited options when accessing mental health services. Furthermore, resettlement in rural and regional locations increased the risk of experiencing many interrelated factors associated with adverse mental health outcomes and distress, including very limited access to support services, with the latter being identified as vital for well‐being. Conclusion: This review highlights the disparity between the Australian Government's policies and plans regarding regional resettlement, what is happening on the ground, and identifies key gaps in research and practice which must be addressed.